ANALYSIS POSSIBILITY OF GAMES INDUSTRY ACQUISITION AS GROWTH STRATEGY OF PT. TELEKOMUNIKASI INDONESIA TBK IN DIGITAL PRODUCTS&SERVICES - Adiningsih, Neni
Almost all telecommunication companies are currently facing the challenge of how to manage their network cost because the growth of data traffic is not proportionally followed by revenue growth. Telkom Group facing challenging situation where its revenue was declining, although the consolidated revenue still has positive growth because weakening business in telecommunication industry in Indonesia, and decreasing Telkom Group’s legacy business revenue such as voice and SMS. Aligned with Corporate Strategic Scenario of TELKOM which is targeting to be Fortune 500, the company must have minimum revenue 324T IDR. This situation enforces Telkom Group to create several growth strategies in order to survive in the digital era of telecommunication industry and to maintain the competitive advantage of a company through TIMES (Telecommunication, Information, Media, Edutainment, Services) portfolio. TIMES market is growing quickly, but the value of TELKOM is shifting into ‘Digital’. Digital products and services, such as IoT, Cloud service, Games, Video Content, etc, are believed able to generate higher data traffic and will impact infrastructure investment to support huge bandwidth, so TELKOM focuses in excellent network development for service delivery, build smart platform for service enabler and invest on innovative product solution to drive digital business. This research is focusing on games industry acquisition, because mobile/PC gaming is rising in popularity recently. Based on Newzoo , gaming research company, total global games market is expected to grow from $137.9 billion in 2018 to more than $180.1 billion in 2021. Newzoo1 estimates there are about 2.3 billion gamers across the globe. Authors is seeing this market as a growth opportunity for TELKOM to drive its digital products and services. According to TELKOM's Strategic Initiatives: Intensifying Smart Inorganic, merger and acquisition is TELKOM’s growth strategy to expand business portfolio in order to create new revenue stream for TELKOM. This research aim is to do analysis the potential values (synergies) and possible risks of acquisition transaction between TELKOM and some games industry as the targeted companies. Based on company valuation analysis using Discounted Cash Flow (DCF) method and merger calculation of Bloomberg Professional application, Capcom Co. Ltd. is the best company among all the targeted companies that potential to be acquired. The result of its estimated enterprise value is steady for 5 years projection and according to proforma analysis the combination company give accretive result to combined company financial. In addition, as reported in Newzoo , Capcom Co. Ltd. is categorized as top 25 public companies by game revenues with 49% YoY growth. This research also analyses the potential synergies and possible risks that must be considered by TELKOM on the process of acquisition. The result of the research concludes that in order to develop new revenue stream in digital product and services, especially on the games industry, TELKOM must deal with M&A, because it is the fastest path to create new business and to enter into new or existing market. Moreover, TELKOM must be selective to decide the targeted company to be acquired and must consider the potential synergy to ensure the synergy probabilities in more details in the due diligent steps to prevent the possible risks.